Kemampuan reproduksi dan riwayat hidup kutukebul Bemisia tabaci (Gennadius) dengan dan tanpa kopulasi pada tanaman cabai merah dan tomat - Purnama Hidayat; Rika Ludji; Nina Maryana (Jurnal Entomologi Indonesia, 2020)
The sweet potato whitefly, Bemisia tabaci (Gennadius) is a cosmopolitan pest on various types of agricultural crops. The whitefly is able to cause damage to plants by directly consuming plant parts using stylet and as a vector of plant viruses. Red chili (Capsicum annuum) and tomato (Solanum lycopersicum) plants are important horticultural plants that are often infested by B. tabaci. Whiteflies are known to reproduce with copulation that produce male and female offspring and without copulation that produce male offspring. The purpose of this study was to determine the reproduction ability of B. tabaci with and without copulation in red chili pepper and tomato. Adult of B. tabaci was taken from a greenhouse in Cikabayan, IPB Dramaga. One female who just emerged from the pupa or final instar nymph was invested in red chilli and tomato plants in polybags to determine the B. tabaci offspring produced without copulation. The same method was also done for whitefly with copulation, but using a pair of adult whitefly (male and female). Each treatment was repeated 5 times. Observations were made every day on the number of eggs produced by one female adult per day, the egg incubation period, the length of the nymph period for each instar, pupa, and adult. The results of this study showed that the fertility of B. tabaci which reproduces with and without copulation in tomato plants was higher than in chili pepper plants, but there was no difference in life cycle and sex ratio.